Pengaruh Literasi Keuangan Dan Financial Teknologi Terhadap Perilaku Keuangan - Aryanti, Meli; Kartini, Tina; Indrawan, Andri (Universitas Muhammadiyah Metro, 2024)
This study aims to determine and explain the effect of financial literacy and financial technology on financial behavior in accounting students. This research is an associative quantitative study using primary data collected through questionnaires. The population in this study were active students of the Accounting Study Program, Faculty of Economics, Muhammadiyah University of Sukabumi, even semester, namely 390 students. the sample in the study was 80 people. The sampling technique was purposive sampling and analyzed through multiple linear regression.The results of this study stated that partially financial literacy had a positive effect on the financial behavior of accounting students, as evidenced by the value of the regression coefficient of 5.086 > 1.9908 and a significance value of 0.000 <0.05, and financial technology has no effect on financial behavior as evidenced by a regression coefficient value of 0.764 <1.9908 and a significance of 0.00 Meanwhile, the financial literacy and financial technology variables simultaneously influence the financial behavior of Accounting Students at the Muhammadiyah University of Sukabumi of 31,384 with a significance of 0.00.